Comparison of measured and computed beam ion current densities emitted from two 2 kJ plasma focus machines - Akel, M.; Alsheikh Salo, S.; Ismael, Sh.; Saw, S. H.; Lee, S. (Elsevier, 2016)
Computed results of beam ion current density are compared with the measured values for a range of pressures (0.13–1.33 mbar) and a range of distances (3–9 cm) downstream of the plasma compression commonly called the pinch in literature dealing with electromagnetically compressed dense plasmas. Partial agreement is found to an extent not reported before. Computed and measured values of ion current densities of the order of 107 Am−2 are found. Moreover the results indicate that detectors should not be placed closer than two anode radii from the position of the plasma focus pinch to avoid interference with the pinch dynamics. The maximum power flow density is found to range from 1012 to 1014 Wm−2. The damage factor (heat flux factor) reach 109 - 1010 Wm−2s0.5 at the pinch exit, while the power flow densities and damage factor values decrease to around 1010 Wm−2 and 106 Wm−2s0.5, respectively, at the distances from the anode top more than 6 cm.